(untitled) (Journal Of Educational and Psychological Researches, 2016)
Education represents a different their areas, especially after the educational cornerstone of Staff of the community in which young person’s that can stand up and shared the overall development process. In order for education to be effective in the community, there is a need to develop to cope with the process development of civilization and modern technology. And for that to be achieved the goal of current research to stand on the advancement of the educational process through Knowledge of educational strategies that had previously requirements put forward for the development of educational process as well as through Knowledge of the most recent development of educational process as. In order to reach these goals ensures Find three chapters and a conclusion. First chapter discusses the general framework of the study; while the second chapter is devoted to view the educational development strategies, either in the third quarter were a new educational trend, and the conclusion, the results presented.